Efektivitas Penerapan Sistem Informasi Akuntansi Pada Bank Perkreditan Rakyat Sari Jaya Sedana Klungkung - Larasdiputra, Gde Deny; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2014)
Attainment of the effectiveness of the application of Accounting Information Systems a good and sufficient corporate needs is a necessity that must be achieved by the company to be able to produce financial information that is accurate, relevant and timely . There are six factors that influence the effectiveness of the application of Accounting Information Systems . Tion, six factors are data security, time, accuracy, relevance, report variation and physical comfort . The purpose of this study was to assess the effectiveness of computer -based accounting information system on the BPR Sari Jaya Sedana Klungkung . Analysis techniques are used to quantify respondents' previous assessment data are qualitative , performed using a Likert scale . The results of this study showed that all six factors influence the effectiveness has been effective in achieving the criteria in this study . This can help the company produce financial information that is accurate, relevant and timely internal and external
Keywords: Effectiveness , Safety Data , Time , Accuracy , Variety reports , Relevance , Physical Comfort , Accounting Information Systems